The effectiveness of work stress coping strategies : An analysis of probit model - Thi, Lip Sam; Lim, Hock Eam (Universiti Utara Malaysia, 2003)
This study finds that the work stress levels that are faced by ICT personnel range from mild to moderate. The estimated probit model finds that there is personality differentiation in the effectiveness of stress coping strategies. The significant and effective coping strategy. is "'seeking treatment". The "escape from situation" coping strategic is found to be significant but ineffective. Thus, it is recommended that in alleviating work stress, "seeking treatment" is the best strategy It is found that the high risk group that have higher work stress are non-Malays, married, field of specialization of accounting/business/ economics, job status of junior management, and less than 2 years of services.